2020
DOI: 10.21203/rs.3.rs-49608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and Distribution of Medicine Vendors in Nigeria: A study of Lagos and Kaduna States.

Abstract: Background In 2014, Nigeria issued the task-shifting/sharing policy for essential health services, which aimed to fill the human resource gap and improve the delivery of health services across the country. This study focuses on the characteristics, spread, and Family planning (FP) stocking practices of medicine vendors in Lagos and Kaduna, assessing the influence of health training on the provision and stocking of FP services and commodities by vendors. Methods We conducted a census of all patent and proprie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As Nigeria continues to pursue the Universal Health Coverage (UHC) goals and make healthcare more accessible, existing data has shown that the role of PPMVs has become more important [19,20], although not always recognized as front-line health workers in Nigeria and other sub-Saharan countries. Medicine shops often serve as an alternative source of healthcare in settings where there are healthcare system gaps (including human resource shortage) and are usually the closes care options in most communities [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As Nigeria continues to pursue the Universal Health Coverage (UHC) goals and make healthcare more accessible, existing data has shown that the role of PPMVs has become more important [19,20], although not always recognized as front-line health workers in Nigeria and other sub-Saharan countries. Medicine shops often serve as an alternative source of healthcare in settings where there are healthcare system gaps (including human resource shortage) and are usually the closes care options in most communities [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As Nigeria continues to pursue the Universal Health Coverage (UHC) goals and make healthcare more accessible, existing data has shown that the role of PPMVs has become more important [19,20], although not always recognized as front-line health workers in Nigeria and other sub-Saharan countries. Medicine shops often serve as an alternative source of healthcare in settings where there are healthcare system gaps (including human resource shortage) and are usually the closes care options in most communities [19][20][21][22][23]. Findings from a recent study by Daini and colleagues showed that the distribution of PPMV shops in the southern and northern parts of Nigeria is far above twice that of the most populous health facilities; ranking 32 and 46 per 100,000, respectively, in Lagos (from Southern Nigeria) and Kaduna (from Northern Nigeria), and have continued to grow progressively in recent years compared to other traditional health facilities, thereby becoming the most accessible health facility for potential clients for different healthcare services [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations